Conscious or indifferent – concerns on digitalisation and sustainability among SMEs in Industry 4.0 - Tick, Andrea; Saáry, Réka; Kárpáti-Daróczi, Judit (Serbian Journal of Management, 2022)
The positive benefits of digitalisation are nowadays generally recognised and acknowledged by companies and are typically seen as essential in a rapidly and constantly changing business environment. Yet the level of digitalisation is still below expectations, especially among small and medium-sized enterprises. Several factors are behind it, ranging from high-cost concerns and management styles to a lack of knowledge etc. The present study reviews one of these aspects, the contradictory relationship between digitalisation and sustainability, with the aim of exploring the potential of digitalisation in the future and outlining new development strategies for small organisations. This research explores the perceived impact of digitalisation on sustainability based on the opinions of SME owners and managers in the V4 countries, Bulgaria and Serbia, using a quantitative method through a questionnaire survey. Based on their perception on the topic, the surveyed organisations can be divided into two groups (Concerned Inspired, Indifferent Conservatives) and accordingly can achieve a state of balanced digitainability, where both sustainability and digitalisation performance are outstanding with different strategic steps.